Mapping the impacts of recurrent floods and windstorms in Bauchi, Nigeria: a hybrid multi-criteria approach using fuzzy-AHP - Kafi, Kamil Muhammad (Frontiers Media SA, 2026)
This study explores the spatial distribution and severity of Weather and Climate Extreme Events (WCEE) in Bauchi city, Nigeria, with a particular focus on flood and windstorm disasters from 2018 to 2023. Using a GPS device, the study identified and recorded the location of 1,236 buildings and structures affected by windstorms and 526 buildings and areas affected by annual floods. Through the utilization of decision-making analytical techniques such as Fuzzy Analytic Hierarchy Process (AHP) and Inverse Distance Weighting (IDW) spatial interpolation techniques, the study assesses patterns, severity, and exposure impacts of WCEE in Bauchi. The findings reveal significant disparities in the impacts of flood and windstorm hazards across different neighborhoods, with certain areas experiencing more severe impacts. The pattern shows that areas with inadequate drainage infrastructure or where residential buildings encroach upon water channels experience severe flood impact, while organic settlements characterized by compact housing, dense population, and non-compliant buildings within the traditional city and suburban areas are more impacted by windstorm disaster. This study further emphasized the strong connection between urban planning and urban disaster vulnerability, risk, and exposure and underscores the urgent need to integrate the ground realities of present and past disaster- and hazard-prone areas in Bauchi with spatial planning initiatives. Through collaborative efforts among planners, policymakers, and stakeholders to co-design and implement effective planning and disaster risk reduction solutions, the city’s resilience to future WCEE can be enhanced.